Situation Report: Hungary, 18 July 1979 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. The Central Committee's Recent Economic Survey Church Policy and the Religious World View Summer Universities: Study and Relax Survival of Quantitative Approach Hampers Food Exports Grain Crop for Bread Poorer than Planned